A surgeon in the village : an American doctor teaches brain surgery in Africa - Bartelme, Tony.; Hoek-Ellegala, Catharina (Boston : Beacon Press, 2017)
The story of how U.S. trained brain surgeon Dilantha Ellegala practiced in Tanzania.
The call -- See one -- Do one -- Teach one.
Includes bibliographical references.
Keywords: Ellegala, Dilantha B; Neurosurgeons -- United States -- Biography; Nervous system -- Surgery -- Tanzania; Medical care -- Tanzania; Print books